Case report: pembrolizumab-induced Type 1 diabetes in a patient with metastatic cholangiocarcinoma. (September 2017) - Smith-Cohn, Matthew A; Gill, David; Voorhies, Benjamin N; Agarwal, Neeraj; Garrido-Laguna, Ignacio
Background:  Immune checkpoint inhibitors are novel cancer therapies associated with numerous autoimmune toxicities, some of which are only now being appreciated.Case presentation:  A 67-year old female with metastatic cholangiocarcinoma and no prior history of diabetes was treated with leucovorin, fluorouracil, oxaliplatin and pembrolizumab. After eight cycles, she developed new onset type 1 diabetes mellitus with positive glutamic acid decarboxylase antibody titers. Conclusions:  To our knowledge, this is the first reported case of PD-1 inhibitor associated Type 1 diabetes mellitus in a patient with cholangiocarcinoma and supports others' experiences that PD-1 inhibition can cause a spectrum of autoimmune adverse events that require clinical monitoring and periodic screenings.